2018
DOI: 10.1016/j.jcjo.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness changes following cataract surgery using swept source optical coherence tomography

Abstract: There was a gradual increase in SFCT at 1 month after cataract removal in the study eyes. The effect was more pronounced in younger individuals and nondiabetic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
5
2
Order By: Relevance
“…Ibrahim et al [54], using EDI-OCT, found that SFCT was significantly increased 1 week after PE and returned to the preoperative level at month 3 after surgery. However, conflicting results have been reported in studies on postoperative SFCT changes in diabetic patients, with some studies showing that SFCT increased after PE surgery in diabetic patients [55,56], while others have found no change [57,58], and yet others have shown a postoperative reduction in choroidal thickness [17]. In the present study, the SFCT increased at week 1 after surgery in the PE group and began to decline at month 3, but did not return to preoperative levels until month 12.…”
Section: Discussioncontrasting
confidence: 77%
“…Ibrahim et al [54], using EDI-OCT, found that SFCT was significantly increased 1 week after PE and returned to the preoperative level at month 3 after surgery. However, conflicting results have been reported in studies on postoperative SFCT changes in diabetic patients, with some studies showing that SFCT increased after PE surgery in diabetic patients [55,56], while others have found no change [57,58], and yet others have shown a postoperative reduction in choroidal thickness [17]. In the present study, the SFCT increased at week 1 after surgery in the PE group and began to decline at month 3, but did not return to preoperative levels until month 12.…”
Section: Discussioncontrasting
confidence: 77%
“…Other authors have analyzed postoperative CT changes in eyes without retinal pathology and found a significant increase in CT. Some authors have declared a prolonged significant increase in subfoveal CT (SFCT) after phacoemulsification [20,29,30]. Similar to our results, Abdellatif and coworkers have published that SFCT increased statistically significantly after 1 month (p = 0.014) with no significant change 3 months after the surgery (p = 0.073) [21].…”
Section: Discussionsupporting
confidence: 88%
“…There was a tendency for decreased postoperative OPP values; however, the OPP measurements at different postoperative follow up points differed significantly in neither group. Literature data shows opposite results of an increase in OPP due to the decrease in IOP [29]. In our study, there was a reduction in OPP after surgery in both groups, indicating not only a postoperative IOP change but also the MAP impact on OPP.…”
Section: Discussioncontrasting
confidence: 65%
“…Cataract surgery was capable of affecting the posterior segments of eyes in rodents and humans; especially, pseudophakic cystoid macular edema (PCME) was a common complication of cataract surgery [7, 30, 31]. Studies [1120] showed an increase in SFCT after cataract surgery in humans, though the mechanism for the increase in the choroid thickness after cataract surgery remained unknown. What are the possible mechanisms?…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to assess the influence of cataract surgery to subfoveal choroid thickness (SFCT). Studies [1120] reported that most patients with senile cataract were expected to maintain increased SFCT for several months after cataract surgery, suggesting the inflammatory response of the surgery or the onset of AMD, which was originated from the choroid layer. However, several studies [2123] hold a different view that no significant increase was detected in SFCT after the surgery.…”
Section: Introductionmentioning
confidence: 99%